Tunable Plasmonic Bandwidth Broadening via DC Electrical Bias - Chen Wei; Fuhua Gao; Fan Yang (Nanomaterials)
The ability to broaden the bandwidth of nanodevices holds significant promise for applications in modern science and technology. In this work, we demonstrate a tunable approach to the bandwidth modulation of nanoresonators by applying a direct current electric field. Quantum hydrodynamic theory reveals that the biased electric field redistributes surface charges, inducing positively and negatively charged regions on the metal surface. This charge asymmetry splits the plasmonic modes, resulting in bandwidth broadening. The optical response can be finely tuned by varying the amplitude and polarization direction of the bias field. This mechanism offers a versatile strategy for developing nanodevices, including metasurfaces with dynamically adjustable bandwidths.